2011
DOI: 10.1007/s10549-011-1401-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and breast reconstruction: a meta-analysis

Abstract: To cite this version:M Barry, M. R. Kell. Radiotherapy and breast reconstruction: a meta-analysis. Breast Cancer Research and Treatment, Springer Verlag, 2011, 127 (1) databases were searched and cross-referenced for appropriate studies where morbidity following BR was the primary outcome measured.. Results:1,105 patients were identified from 11 appropriately selected studies.Patients undergoing PMRT and BR are more likely to suffer morbidity compared to patients not receiving PMRT ((OR) = 4.2; 95% CI, 2.4-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
13

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(143 citation statements)
references
References 38 publications
3
127
0
13
Order By: Relevance
“…However, autologous breast reconstruction provides reduced morbidity than implantbased reconstruction in the setting of postoperative radiotherapy (2,26). In the present study, no patients received radiotherapy after the breast reconstruction, only before.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, autologous breast reconstruction provides reduced morbidity than implantbased reconstruction in the setting of postoperative radiotherapy (2,26). In the present study, no patients received radiotherapy after the breast reconstruction, only before.…”
Section: Discussionmentioning
confidence: 66%
“…Radiotherapy after mastectomy but before reconstruction has not been shown to increase complications of the flaps after autologous reconstruction (25), although not all studies agree on this (26,27). However, autologous breast reconstruction provides reduced morbidity than implantbased reconstruction in the setting of postoperative radiotherapy (2,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors suggest that patients with postoperative complications, such as those with large breasts for whom a maximum dose of < 107% is not achievable, or patients with breast implants who have an increased risk for late fibrosis or cosmetic deterioration following radiotherapy, should receive a biologically less-intense dose 94 . Adjuvant radiotherapy after breast reconstruction (especially implant-based) is a risk factor for higher tissue toxicity 95 .…”
Section: Radiotherapymentioning
confidence: 99%
“…Barry and Kell in a meta-analysis of 11 studies found that patients receiving postmastectomy radiotherapy (PMRT) after implant reconstruction had significantly increased risk of complications (odds ratio [OR] 4.2; 95 % CI 2.4-7.2) compared with those who did not receive radiation. 3 Autologous reconstruction was associated with less morbidity (OR 0.21; 95 % CI 0.1-0.4) in the setting of PMRT. The impact of radiation therapy on implant breast reconstruction from the patients' perspective is less well documented.…”
mentioning
confidence: 93%